MINERAL DIETARY STATUS OF SOME EXISTING DOMESTIC WHEAT GENOTYPES - Imtiaz, M.; Khan, P.; Depar, N.; Siddiqui, S. H.; Memon, M. Y.; Aslam, M.; Shah, K. H.; Naqvi, M. H.; Babar, H. (The Nucleus, 2020)
Mineral elements like Cu, Fe and Zn are very crucial for human health and play a key role in various biochemical processes. The daily dietary requirement of a young adult ranges from 10-60 mg for Fe, 2-3 mg for Cu and 15 mg per day for Zn. Intake less than these values can slower physiological processes. The information on the reserves of these elements in staple foods like wheat is scarce. The present study was undertaken to collect such information for wheat and 78 genotypes were analyzed for these nutrients. The results revealed that Zn concentration in seed ranged between 30.4 to 55.5 Î¼g g-1 in 31 genotypes, from 21.08 to 29.8 in 37 genotype and from 12.72 to 19.08 in 10 genotypes. Of the different genotypes, 38 were recorded as poor in Zn and ranged from 0.41 to 1.06 Î¼g Zn/seed. Rests of the genotypes were either medium or rich in Zn. Considerable variations in Fe and Cu concentrations were also observed in seed of different genotypes. Iron concentration ranged from 13.03 to 52.43 Î¼g g-1 while Cu concentration averaged between 2.66 and 6.10 Î¼g g-1.